2020
DOI: 10.3390/microorganisms8071013
|View full text |Cite
|
Sign up to set email alerts
|

Equine Alphaherpesviruses Require Activation of the Small GTPases Rac1 and Cdc42 for Intracellular Transport

Abstract: Viruses utilize host cell signaling to facilitate productive infection. Equine herpesvirus type 1 (EHV-1) has been shown to activate Ca2+ release and phospholipase C upon contact with α4β1 integrins on the cell surface. Signaling molecules, including small GTPases, have been shown to be activated downstream of Ca2+ release, and modulate virus entry, membrane remodeling and intracellular transport. In this study, we show that EHV-1 activates the small GTPases Rac1 and Cdc42 during infection. The activat… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
7
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 14 publications
(7 citation statements)
references
References 63 publications
(95 reference statements)
0
7
0
Order By: Relevance
“…In the horse, a few studies about α4β1 integrin are available [26][27][28][29][30][31][32], and are related to its presence on leukocytes [26,29] and endometrial epithelial cells [27,28] or equine herpesvirus 1 infection mechanism [30][31][32]. Integrins represent one of the most important families of cell adhesion receptors that mediate cell-cell and cell-ECM interactions.…”
Section: Discussionmentioning
confidence: 99%
“…In the horse, a few studies about α4β1 integrin are available [26][27][28][29][30][31][32], and are related to its presence on leukocytes [26,29] and endometrial epithelial cells [27,28] or equine herpesvirus 1 infection mechanism [30][31][32]. Integrins represent one of the most important families of cell adhesion receptors that mediate cell-cell and cell-ECM interactions.…”
Section: Discussionmentioning
confidence: 99%
“…We investigated Cdc42 GTPase, a well-studied signaling protein that regulates filopodia formation and actin rearrangement [23,24]. Cdc42 plays a role in the infectious process for several viruses, including HIV-1, HSV-1, EHV, EBV, HHV-8, strains of VACV, DEV-2, and RSV [25][26][27][28][29][30]. Using a PAK-PBD pulldown assay for active Cdc42, we demonstrate that there is an increase in GTP bound Cdc42 after 15 min of virus addition in HaCaT cells.…”
Section: Discussionmentioning
confidence: 99%
“…Previous studies have shown that Cdc42 inhibitor ML141 does not block virus entry, but rather inhibits virus transport to the nucleus of α-herpesvirus equine herpesvirus type 1. 54 Additionally, studies have shown that B-Raf V600E inhibitors can interact with Ras-GTP. 55 This finding suggests that RAF265 targets Cdc42 via a Ras-mediated interaction, which prevents the nuclear import of HSV-1.…”
Section: Raf265 Presented Relatively Broad Antiviral Activitymentioning
confidence: 99%